Management and Treatment recommendations for World Health Organization Grade III and IV gliomas - Altwairgi, Abdullah K; Raja, Shanker; Manzoor, Mohammed; Aldandan, Sadeq; Alsaeed, Eyad; Balbaid, Ali; Alhussain, Hussain; Orz, Yassir; Lary, Ahmed; Alsharm, Abdullah A. (International Journal of Health Sciences, 2017)
The treatment recommendations provided in this manuscript are intended to serve as a knowledge base for clinicians and health personals involved in treating patients with high-grade malignant glioma. In newly diagnosed patients, complete resection or biopsy is required for histological characterization of the tumor, which in turn is essential to decide the treatment strategy. In patients with good or borderline performance score, radiotherapy (RT), and chemotherapy are the preferred management. In patients with poor performance score, RT with best possible supportive care is the mainstay of the management. All patients have to undergo brain magnetic resonance imaging procedure quarterly or half‑yearly for 5 years and then on an annual basis. In patients with recurrent malignant glioma, wherever possible re-resection or re-irradiation or chemotherapy can be considered along with supportive and palliative care. High-grade malignant glioma should be managed in a multidisciplinary center with the best of the possible care that is available based on the evidence as discussed in this manuscript.